БЕЗДАТЧИКОВЕ КЕРУВАННЯ ВЕНТИЛЬНИМИ РЕАКТИВНИМИ ДВИГУНАМИ ТЯГОВИХ ЕЛЕКТРОМЕХАНІЧНИХ СИСТЕМ - Сінчук, О.М.; Козакевич, І.А.; Юрченко, М.М. (Інститут електродинаміки НАН України, Київ, 2017)
In the paper a sensorless control system of switched reluctance motors, which can be used in the structure of traction electromechanical systems, is proposed. This modify of sensorless control allows to simplify the structure of the electromechanical system, estimating the magnitude of the rotor angular position using measured electrical parameters eliminating the need of use a position sensor on the motor shaft. The position estimating is performed using the identification of the change of winding inductances of the traction electric machine when the test voltage pulses are applied. The efficiency of the proposed solutions is proved by mathematical modeling. References 10, figures 4.